Value Transformation in Fulfillment of Children Rights Through Child-Friendly Village - Kusumawardani, Erma; Prasetyo, Iis (Universitas Muhammadiyah Surakarta, 2018)
Childhood is a special phase concerning both in the process of physicalgrowth and soul. Children are not only the responsibility of the parents but thestate for the fulfillment of rights. Thus, the fulfillment of childrenâs rights becomesan interesting issue. To give a meaning of natural condition in place of research,this research used a qualitative approach with phenomenology research type. Thisresearch concern on nonformal education for children. Child-friendly village as aneffort to realize the city worthy of children is one of the solutions in fulfilling the rights of the children. As a result, the transformation of values from the fulfillment of childrenâs rights increasingly improved through a child-friendly village. The transformation of values includes transformation from adults to children, from groups to individuals, and from individuals to individuals involved in activities. Transformed values include discipline, courage, confidence, mutual respect, and cooperation.